Correlation of PET-CT nodal SUVmax with p16 positivity in oropharyngeal squamous cell carcinoma. Issue 1 (December 2015) - Clark, Jessica; Jeffery, Caroline; Zhang, Han; Cooper, Tim; O'Connell, Daniel; Harris, Jeffrey; Seikaly, Hadi; Biron, Vincent
Abstract Background The incidence of human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) has been rising in recent years. Given the clinical impact of HPV/p16 positivity in OPSCC, identifying surrogate markers of this disease early in the diagnostic work-up of these patients could improve patient care. Methods Demographic, pathologic, staging and PET-CT data from patients diagnosed with OPSCC from 2009–2014 were obtained from a prospectively collected provincial cancer registry. Tumor HPV/p16 status was correlated to the maximum standard uptake value (SUVmax) of the primary tumor and cervical nodes. Comparisons of means and multinomial regression models were used to determine associations between p16 status and SUVmax. A diagnostic odds ratio was calculated using a cut off value for predicting HPV/p16 positivity based on nodal SUVmax. Results PET-CT and HPV/p16 data was obtained for 65 patients treated surgically for OPSCC. Significantly higher nodal SUVmax was associated with HPV/p16 positive nodes (SUVmax 10.8 vs 7.9). No significant differences were seen between HPV/p16 positive vs negative primary tumor SUVmax (10.3 vs 13.7). In combination with other clinical parameters, higher nodal SUVmax was highly correlated with HPV/p16 positivity. Conclusion Elevated nodal SUVmax is a significant predictor of HPV/p16 positive disease.